Hybrid almost output regulation of linear impulsive systems with average dwell-time. (May 2016) - Yuan, Chengzhi; Wu, Fen
Abstract: This paper deals with the hybrid almost output regulation problem for a class of linear systems with average dwell-time impulses. The proposed hybrid output regulator is constructed as a linear impulsive system that undergoes synchronous impulses with the controlled plant. Lyapunov-based sufficient conditions of the output regulability and weighted L 2 performance for the linear impulsive systems are first derived. Based on the analysis results, the hybrid synthesis problem is formulated in terms of linear matrix equations plus a set of linear matrix inequalities (LMIs). With this hybrid synthesis scheme, both flow and jump dynamics of the hybrid regulator can be jointly designed by solving a convex optimization problem in minimizing the weighted L 2 gain from the perturbation signal to the error output. A numerical example is used to demonstrate the proposed approach.